The Discourse and the Capitalist. Lacan, Marx, and the Question of the Surplus - Bianchi, Pietro (Filozofski vestnik, 2011)
In the seminar XVI, D'un Autre à l'autre, in 1968/1969, Jacques Lacan claimed that there is an homology between the function of object a in the unconscious and the Marxian notion of surplus-value. Both concepts in fact revolve around similar axes: their reluctance to be localized in a certain place of the structure and their connection with the notion of surplus. In Chapter 7 of Das Kapital, Marx seems to imagine a purely mythical pre-capitalist society where production is only devoted the pure satisfaction of basic survival needs and where labour is still controlled by the worker according to a certain purpose: with the irruption of the surplus in the capitalist mode of production the very qualitative dimension of the production and reproduction of commodities and human beings is commanded and organized by the pure drive of abstract accumulation. In order to rearticulate the incessant capitalist drive for abstract wealth, the symptom relies on the unsurpassable contradiction between labour-power and living-labour: essential in order